The Effect of Recruitment and Motivation Systems on the Productivity of Permanent Lecturers at the PTIQ Institute Jakarta - Lili Sularmi; Eri Anggraini (Journal of Research in Business, Economics, and Education, 2020)
The purpose of this research to find out the influence recruitment system and motivation for the work productivity of permanent lecturers at the Institute PTIQ Jakarta either partially or simultaneous. The method used in this research is quantitative descriptive, while the data collection in this research is a questionnaire with a measurement scale that is the Likert scale. The entire population in the research as respondents totaling 96 lecturers with permanent status. Then it means that the sample technique used is saturated sample technique. The results showed that there was a significant simultaneous effect between recruitment system and motivation for the work productivity of lecturers in the statistical test the value F count > Fttable was 31,105 > 2,700. Contribution of influence between recruitment system variables and motivation influence the lecturer work productivity variables of 40.1% while the remaining 59.9% is influenced by other factors.